The NLRP1 inflammasome in skin diseases - Burian, Marc; Schmidt, Morna F.; Yazdi, Amir S. (Frontiers in Immunology, 2023)
Healthy human skin is constantly exposed to sterile and microbial agents. The skin immune system plays an important role in immune surveillance between tolerance and immune activation. This is mainly mediated by neutrophils, macrophages and most importantly lymphocytes. However, keratinocytes, which form the outermost skin barrier, the epidermis, are important for cutaneous homeostasis. Being a non-professional immune cell, recognition of danger signals in keratinocytes is mediated by innate immune receptors (pattern recognition receptors, PRR). While Toll-like receptors are located on the cell membrane or the endosomes, Nod-like receptors are intracellular PRRs, some of which, once activated, trigger the formation of inflammasomes. These multiprotein complexes serve as platforms that mediate the release of innate cytokines after successful recognition, thereby attracting immune cells. The most well characterized inflammasome is the NLRP3 inflammasome. The function of inflammasomes differs significantly between different cell types (keratinocytes versus immune cells) and also between different species (human versus mouse). Great effort has been made in recent years about the mechanisms of their activation. Dysregulation of inflammasomes can sometimes lead to severe diseases. Here, we describe diseases associated with dysregulation of the inflammasome NLRP1, which is predominant in keratinocytes.